Incidence, prevalence and clonal susceptibility of Phomopsis canker disease in southern Indian tea plantations - and U.I. BABY, P. PONMURUGAN*, B. MYTHILI GNANAMANGAI (Indian Phytopathology, 2013)
Phomopsis canker is one of the most important stem diseases of tea plants which affect the yield potential significantly. In order to assess the current scenario of Phomopsis canker incidence in southern India tea plantations, a survey was undertaken covering two disease seasons (2002-2006 and 2007-2011). The percentage of diseases incidence (PDI), prevalence and clonal susceptibility of different tea clones and seedlings in various agroclimatic zones were determined. The results indicated that there was a correlation between disease severity and meteorological data and soil sample analysis. The survey clearly showed that different clones / seedlings have different levels of disease severity and their susceptibility varied in various agroclimatic zones. Of the different tea planting districts surveyed, Wynaad and Central Travancore of Kerala were severely affected by the disease. Soil analysis of different tea planting districts showed there was a depletion in balanced nutrients leading to high disease prevalence especially in Wynaad during 2002-2006 and Central Travancore areas during 2007-2011 periods. It has been suggested that the impact of climate change and agronomic practices are the predisposing factors to cause the high disease incidence.